A smartphone application to objectively monitor music listening habits in adolescents - Danique E. Paping; Jantien L. Vroegop; Simone P. C. Koenraads; Carlijn M.P. le Clercq; André Goedegebure; Robert J. Baatenburg de Jong; Marc P. van der Schroeff (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Listening to music through personal listening devices (PLDs) has become more prevalent during last decades. The aim of this study was to evaluate music listening habits through PLDs in adolescents with a smartphone application, and to assess the accuracy of self-reported listening habits. Methods This study was embedded in the Generation R Study, a population-based prospective birth cohort in Rotterdam, the Netherlands. A smartphone application for Android operating systems was developed to objectively monitor music listening habits for a period of 35 days. A postal questionnaire was used to subjectively assess listening habits. The level of agreement between the objectively measured and self-reported listening habits were evaluated using weighted kappa coefficients. Data were collected from May 2017 to March 2019. Results A total of 311 adolescents aged 12 to 15 years were included, of whom 237 (76.2%) completed the postal questionnaire. The results of the smartphone application showed that the median listening frequency was 2.1 days a week (IQR 1.0–3.4), the median listening time 21.1 min a day (IQR 9.1–53.7), and the mean listening level 54.5% (SD 18.1%). There was a slight to fair agreement between the objectively measured, and self-reported listening habits according to the weighted kappa coefficients (k = 0.179 to 0.364). Conclusions The results of the current study suggest that self-reported measures of listening habits are not always accurate. We consider a smartphone application to monitor listening habits of added value in future research investigating the possible damaging effects of PLDs on hearing acuity. Graphical abstract